ANALISIS NILAI TAMBAH PRODUK OLAHAN KENTANG (Solanum tuberosum) DI KECAMATAN CIKAJANG KABUPATEN GARUT - Qisthy Arinal Haq; Eliana Wulandari (Universitas Galuh Ciamis, 2020)
The number of potato processors in Cikajang Sub-district Garut District is still relatively small, while Cikajang Sub-district Garut District is one of the production centers of potato commodities, which means the availability of abundant raw materials and has potential to be processed into other products to create added value. This problem can be caused by lack of information regarding the amount of added value that can be obtained from the processing. Therefore, the purpose of this study is to analyze the business efficiency and added value of potato processing. This study uses a quantitative research design with a questionnaire as a research instrument to 11 potato processors in Cikajang Sub-district, Garut District using the census method in September – November 2019. Data sources used are primary and secondary data. The data collected was processed using the business efficiency analysis method (RC ratio) and Hayami method. The results showed that the efficiency of processing potatoes into potato chips in Cikajang Sub-district was 1.8 and the added value obtained was Rp 10,647.4 / kg of potato raw material with a value-added ratio of 48.04%.